Photoelectron Spectroscopy of the Phosphorus Monosulfide (PS) and Phosphorus Monoxide (PO) Radicals - Recio, Pedro; Alonso de la Fuente, Jorge; Drissi, Myriam; Bulut, Niyazi; Loison, Jean Christophe; Garcia, Gustavo; Zanchet, Alexandre (Wiley-V C H Verlag Gmbh, 2026)
PO and PS radicals are the smallest units of phosphorus oxides and phosphorus sulfides, respectively, two rich families of refractory compounds widely employed in industrial and technological applications. These two diatomic radicals are also thought to be relevant for the phosphorus (P) chemistry in the interstellar medium (ISM). PO is indeed one of the few P-bearing molecules detected in the ISM, while models also predict a considerable abundance of PS, although its presence in the ISM has not been confirmed yet. Since P is an essential element for the development of life, understanding its relatively unknown chemistry in the ISM is essential for astrobiology. The recent detection of PO+ in surprisingly high abundance in the ISM also suggests that the cations are likely to be relevant too for the ISM chemistry of phosphorus. While PO and PO+ are relatively well known, experimental data available in the literature for PS are very scarce and its cation PS+ is mainly unknown spectroscopically, hindering its possible detection in the ISM. In this work, we present slow photoelectron spectra of both species generated in situ in a discharge flow reactor. From these spectra, and with the support of electronic structure calculations, we have determined the adiabatic ionization energy of both radicals (IEPO = 8.377 +/- 0.006 eV, IEPS = 7.904 +/- 0.006 eV) and the spin-orbit splitting of the (2)Pi ground state of PS (350 +/- 34 cm(-1)). We also show that in the case of PO, the splitting is smaller than 250 cm(-1). In addition, relevant information on the vibrational structure of the two cationic ground states is extracted, providing useful spectroscopic data on the two species which might contribute to the ISM detection of these species, their vibrational bands falling within the spectral coverage of the James Webb Space Telescope (JWST).
Keywords: astrochemistry; ionization; phosphorus; photoelectron; radicals